Assistance in the Use of the Quizizz and Mentimeter Platforms to Improve the Competence of Mathematics Teachers in the City of Flores - Nur, Isman M.; Asyraf, M. Fahmi Aufar; Triyono, Ageng; Saleh, Rusmin R.M (LP2M INSURI Ponorogo, 2023)
The background to the implementation of the Community Service Program was the difficulties teachers and prospective math teachers in East Flores City had in designing and managing interactive learning online. So, the main purpose of this service is to increase the competence of teachers and prospective teachers according to the needs of the target community. The dedication stage consists of (1) the Preparation Stage; (2) the Implementation Stage, and; (3) the Practice, Monitoring, and Evaluation Stage. All stages of the service are carried out in the period 1-30 August 2021. The implementation stage of the service is carried out through the webinar method and the implementation of interactive learning designs using the Quizizz and Mentimeter platforms. The target community is 20 people. The Service Team consists of 3 students and one supervisor. One mathematics education expert from Ahmad Dahlan University (UAD) was involved in the implementation stage. Based on the Practice, Monitoring, and Evaluation Stages, it is known that all participants have implemented the webinar material, and more than 85% of participants stated that this service program was very useful and increased competency in designing and managing interactive learning online. Thus it can be concluded that the implementation of community service has achieved the stated goals.